Transorbital Endoscopic Surgery for Sphenoid Wing Meningioma: Long-Term Outcomes and Surgical Technique - Goncalves, N.; Lubbe, D.E. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Sphenoid wing meningiomas are benign tumors that can result in proptosis, visual impairment, and pain. Traditional open surgical approaches are associated with significant morbidity. Transorbital endoscopic surgery has been developed as a minimally invasive approach to gain access to these tumors and address the main presenting symptoms. Case series reporting transorbital endoscopic resection of sphenoid wing meningiomas using combined endonasal, pre-caruncular, and extended superior eyelid approaches have demonstrated stable and/or improved short- and medium-term visual outcomes. Earlier medial optic nerve decompression appears to result in more favorable long-term visual outcomes. Transorbital endoscopic surgery therefore represents an emerging minimally invasive alternative to deal with these challenging lesions.
Keywords: meningiomas; sphenoid wing meningiomas; Transorbital